Trade-Offs and Synergies Between Seagrass Ecosystems and Fishing Activities: A Global Literature Review - Herrera, Mariana; Tubío, Ana; Pita, Pablo; Vázquez, Elsa; Olabarria, Celia; Duarte, Carlos M.; Villasante, Sebastián (Frontiers in Marine Science, 2022)
Seagrasses support human well-being by delivering a wide range of ecosystem services. Particularly important is the role they play in food provisioning by supporting fisheries. Despite their socio-economic importance, it is only recently when they have been considered as important social-ecological systems worldwide. Research focused on the interactions between seagrasses and human activities have been understudied and never addressed from a global approach, even though this knowledge is essential to create relevant policy and management plans, and to promote governance systems, which consider fishers’ needs and rights. We carried out a global systematic review on trade-offs and/or synergies between seagrasses and fishing activities, aiming to analyse the current state of the art on these interactions, to identify potential gaps in knowledge, and to pinpoint key research priorities. We found a total of 94 publications assessing the relationship between seagrass and fisheries, which have tripled between 2001-2021, being most of them empirical studies (90%) with ecological scope (a total of 68). Socioeconomic studies (3%) were identified as a knowledge gap. Most studies (72%) were carried out in northern hemisphere countries, with an underrepresentation of studies in tropical regions. Studies reporting trade-off (a total of 69) interactions almost tripled those reporting synergies (a total of 31) between seagrass and fisheries. Mechanical damage is the main source (51%) of trade-offs, followed by overfishing (28%), while aquaculture emissions (20%) are also a relevant source of trade-offs. Seafood market demand and conflicts of use were the main drivers for trade-offs. When assessing synergistic interactions, most studies (27 out of 31) reported a larger abundance or recruitment of species with commercial interest mediated by seagrass habitat provision. Globally, seagrasses are mainly affected by industrial and small-scale fisheries, including aquaculture and shellfisheries, and to a lesser extent, by recreational fisheries. Fisheries management system is not specified in more than half (53) of the reviewed publications, which represents a key knowledge gap with implications for sustainable management. We document a fast increase in studies covering fishery-seagrass interactions, which, if accompanied by better reporting of the nature of the interactions would help improve the sustainable management of both systems.